Unveiling The Nexus Between Zakat Distribution and Islamic Human Development Index: Implications for Poverty Reduction - HARAHAP, CHOIRUNNISA TRI ANA; CAHYANI, UTARI EVY; SIREGAR, IBRAHIM; MAARIF, MUHAMMAD ARIFUL (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study analyzes the interaction between zakat distribution and the Islamic Human Development Index (I-HDI) on the poverty rate in North Sumatra. The problem addressed in this research is the limited empirical evidence explaining how zakat and human development jointly influence poverty reduction in Muslim-majority regions. Fourteen districts/cities with complete annual data for the four-year period 2019–2022 were selected, producing panel data observations. This study employs the Panel Vector Error Correction Model (PVECM), which is suitable for analyzing causality, interdependence, and adjustment processes within non-stationary panel data. The results show that zakat distribution contributes to reducing poverty, although its effect becomes meaningful only after several periods when the adjustment process converges toward a consistent long-term pattern. Meanwhile, the I-HDI demonstrates a stronger and more persistent influence on poverty reduction, with its impact increasing until it reaches a stable long-run trajectory. The findings also indicate that zakat positively supports improvements in I-HDI, especially in later periods of the analysis. This study highlights the need to improve the efficiency and targeting of zakat distribution and to strengthen collaboration between zakat institutions and government development programs. The novelty of this research lies in the use of the I-HDI, an index based on maqāṣid al-sharī‘ah that integrates spiritual, educational, health, and socioeconomic dimensions, offering a more contextual and holistic measure of human development compared to the conventional HDI.